Instrumental and Hedonic Motives for Emotion Regulation in Musical Practice - Breaden Madden, Gerard; Jabusch, Hans-Christian (Frontiers in Psychology, 2021)
Emotion regulation literature often emphasizes that individuals regulate their emotions for hedonic reasons. However, there is increasing support for an instrumental approach to emotion regulation. This approach suggests that emotions are regulated if they are believed to be beneficial to the pursuit of personally relevant goals. When pursuing a long-term goal, an individual may forego immediate, hedonic emotional reward in order to maximize the instrumental benefits of emotions. The current study investigates emotion regulation behaviour in the context of musical practice. We examine whether musicians adopt specific, regulated emotional stances which support their goal orientation, and which are in line with their beliefs regarding the functional impact of emotions. Via an online questionnaire, 421 musicians reported their goal-orientation, meta-emotion beliefs, and affect-regulation strategies. Participants then completed a scale assessing specific emotions they would regulate in order to support their musical practice. Data were analysed using PCA, MANOVA, subgroup analysis and categorical regression. Musicians reported using affect-improvement strategies more often than affect-worsening strategies in order to influence how they felt during musical practice. Greater reported use of affect-worsening strategies was associated with stronger meta-emotion beliefs supporting the possible instrumental benefits of unpleasant emotions (F = 30.33; p < 0.01; ηp2 = 0.06). Musicians who strongly endorsed this belief more strongly pursued mastery goals in contrast to enjoyment goals. In terms of specific targeted emotions, musicians generally sought to reduce unpleasant emotions, and increase pleasant, energizing emotions in order to support their musical practice. However, a subgroup of mastery- rather than enjoyment-oriented musicians may seek a mixed emotional state, increasing anger and nervousness in conjunction with a number of pleasant emotions (Wilks λ1,420 = 14.42; p < 0.01; ηp2 = 0.50). Musicians who pursue expert musical skills may be motivated to experience emotions that combine the instrumental and hedonic benefits of emotions. Musicians who practice for enjoyment may prioritize emotions that maximize only the hedonic benefits. Future research should aim to identify the regulated emotional states that best support specific musical practice outcomes in an individual. It will also be important to understand on all levels, including music performance quality as well as health and well-being, the outcomes that may be associated with the use of affect-worsening strategies and unpleasant emotions. Research in this field may equip musicians with novel skills for better pursuit of their goals, and may help to maximize health and well-being in musical practice.